THE EFFECT OF STOCK SELECTION SKILL, MARKET TIMING ABILITY, TURNOVER RATIO AND CASH FLOW ON SHARIA MUTUAL FUNDS PERFORMANCE (Case Study of Sharia Mutual Fund Companies Registered in OJK for the Period of 2011-2014) - Mega Mustika Sari; Sri Mulyati; Estu Widarwati (JABI (Journal of Accounting and Business Issues), 2019)
Mutual funds syariah are other investment opportunities with measurable risk and return is high enough with enough capital affordable to the community. Mutual funds syariah have an Investment Manager with the ability and knowledge of the market it is or will happen. Therefore, mutual funds syariah selected by investors because it is cheap, easy and "managed by the experts". This research analysted do stock selection skill, market timing ability, Turnover ratio and Cashflow can influence the performance of equity mutual funds syariah in Indonesia. The data used in this research are data on financial statements , Net Asset Value (NAV), SBI, IHSG, yearly data and prospectus of 10 equity mutual fund syariah that were sampled during this research report from 2011-2014. As a research methodology, we used F test and t test to examine research’s hypothesis, also used assumption classic test there are normality test, autocorrelation test, heteroscedasticity test and multicolinearity test. These results can be viewed on multiple regression analysis and the coefficient of determination, the R value of 0.513 means the relation between the stock selection skill, market timing ability, Turnover ratio and Cashflow to profitability by 51.3%, meaning that the relationship between variables was most closely. Adjusted R Square value of 0.545 which means 54,5% achievement of profitability can be explained by the stock selection skill, market timing ability, Turnover ratio and Cashflow. The remaining 45,5% can be explained by other factors not examined in this research.